PENGARUH PENAMBAHAN SILIKON (Si) TERHADAP SIFAT MEKANIK BAHAN GAMELAN PADUAN PERUNGGU TIMAH PUTIH (CuSn) DENGAN VARIASI KOMPOSISI - Khotim Mahfud; Budi Harjanto; Nyenyep Sri Wardani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
This research has an objective to describe : (1) the effect of silicon addition to tin bronze alloy at an elastic properties; (2) the effect of silicon addition to tin bronze alloy at an impact power; (3) the effect of silicon addition to tin bronze alloy at a micro structure level. The research uses an experimental method with descriptive data analysis. The research sample is the result of tin bronze alloy plus silicon. The independent variables of this research are variations in the addition of silicon 1.5%, 3%, and 4.5%. The dependent variable of this research is tin bronze alloy. The results of this research indicate that the increased elastic properties are influenced by the addition of silicon which is known from the calculation of elastic modulus that the highest is 4.5% silicon variation has increased by 21.218% from tin bronze alloy. Broken toughness through the biggest impact test on the addition of 4.5% silicon has an impact value increase of 53.793%. The addition of silicon has an effect on the mechanical properties of the alloy where the elastic properties and impact strength have increased. The resulting microstructure explains that variations in the addition of silicon have an effect on the phase formed on the mechanical properties of the alloy. With the addition of silicon to tin bronze alloy can be recommended as a substitute for gamelan musical instruments.